Mass Media in Vocational Guidance. Experience of a Korolov Zhytomyr Military Institute - Nosova, Hanna; Loboda, Veronika (Pedagogical Discourse, 2022)
The article explores the possibilities of modern mass communication means taking into account their application in conducting professional-orientation work and entrance campaign in the higher military educational institution. An analysis of target audiences is carried out, which are key to achieving the purpose of the entrance campaign. The unique features of professional-orientation work are presented, inherent in military educational institutions. Discussions arising during the formation of a strategy of campaign campaign, related to the peculiarities of training specialists in the security and defense sector and possible ways to solve them are proposed. A strategy of conducting professional-orientation work with the use of modern means of mass communication by higher education institution is proposed. Practical results obtained when applying the proposed strategy in the vocational-orientation work of the higher military educational institution are presented. The directions of further theoretical research and practical recommendations are formulated to improve the efficiency of the specified work.